Environmental security in the Artic Ocean promoting co-operation and preventing conflict - Berkman, Paul Arthur (Whitehall paper, 2010)
The North Pole is being transformed from a sea-ice cap to a seasonally ice-free sea within the next few decades. This fundamental shift in the boundary conditions of the Arctic Ocean will create a new natural system with different dynamics than anything previously experienced by humans in the region. With the diminishing ice cover, interests are awakening globally to take advantage of extensive energy, shipping, fishing and tourism prospects in the Arctic Ocean. A range of states, including the major Arctic powers, are increasingly asserting their sovereignty seawards. National security policies are being declared and nuclear-capable states are adjusting their strategic deployments in the Arctic Ocean.